Catalytic and metal-free intramolecular hydroalkoxylation of alkynes. Issue 7 (14th February 2019) - Jean, Alexandre; Rouden, Jacques; Maddaluno, Jacques; De Paolis, Michaël; Blanchet, Jérôme
Graphical abstract: Highlights: Metal-free synthesis of exocyclic enol ethers. Simple catalyst and reaction conditions. Microwave assisted unusual hydroalkoxylation of linear alkynes. Fast and stereoselective process. Abstract: Benzyltrimethylammonium hydroxide act as an efficient metal-free catalyst for the intramolecular hydroalkoxylation of alkynes. Notably, the use of microwave irradiation allowed reaction to operate in only two minutes. Under optimized reaction conditions, linear alkynes bearing aryl and heteroaryl substituents were successfully cyclized with good level of stereoselectivity.